IMPLEMENTASI SISTEM ZONASI PENERIMAAN SISWA SMA DI KABUPATEN BELITUNG TIMUR - Parno Suparno; Wangsih Wangsih (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
This study aims to address the problems of the zoning system on the admission of high school students in East Belitung Regency in the 2018-2019 school year. How is the implementation of the zoning system carried out by the Bangka Belitung Provincial Education Office, the factors that hinder the implementation of zoning, and its impact on education services and quality in East Belitung Regency. The method used in this research is descriptive with an inductive approach. This research describes and explains the situation or reality that actually happened at the research location systematically, factually and accurately. General conclusions based on data or factors that are specific to the problem at hand. The operational concept in this research is based on Grindle's implementation theory (1980: 11), which has dimensions and content of the implementation context. The results show that in terms of content and context in general school principals, teachers, parents and students mostly or 75.17% agree with the Zoning system as stated in the statement, 16.51% feel doubtful and 7.94% disagree. The inhibiting factors for the implementation of the zoning system for high school student admission in East Belitung Regency are: uneven socialization of the zoning system, mindset of teachers, parents, students who have not shifted from the old conditions, there is no accurate guidance and uneven problems. The impact of the zoning system on the quality of education has not yet been seen because it has not yet produced graduates. Keywords: zoning system, student acceptance, east belitung.